The effect of swirl intensity on flame propagation behavior in lean premixed burner - Yuichi ICHIKAWA; Masaharu KOMIYAMA; Atsushi KOYAMA (Nihon Kikai Gakkai ronbunshu, 2015)
In gas turbine engines, combustion temperature increases in order to reduce CO2 emissions and to improve thermal efficiency. However, at the same time, this leads to the increase of nitrogen oxide (NOx) emissions. Lean premixed combustion is one of the most effective techniques to reduce NOx emissions. However, lean premixed combustors have a narrow stable combustion range compared with diffusion combustors and have a risk of flashback. Flashback of flame into the fuel nozzle causes serious damage to combustors. In this study, we present characteristics of unsteady flame behavior in a premixed burner with swirling flow. A variable swirler is used in order to investigate the flame behavior under different swirl intensity. The relationship between the flame behavior and flow fields in the premixer have been captured by applying high-speed particle image velocimetry (PIV) measurement. It is clarified that flow velocity of unburned gas upstream the flame tip has effect on flame propagation velocity regardless of swirl intensity from the results of PIV measurement in flashback limit. From the results of PIV measurement in blow-off limit, we clarified the possibility of flame extinction upstream the flame tip in high swirl intensity. It is conceivable that this is because flame is stretched by a steep velocity gradient.